The China problem in postwar Japan : Japanese national identity and Sino-Japanese relations - Hoppens, Robert James (SOAS studies in modern and contemporary Japan., 2015)
The China Problem in Postwar Japan challenges some common assertions or assumptions about the role of Japanese national identity in postwar Sino-Japanese relations, showing how the history of Japanese relations with China in the 1970s is shaped by the strength of Japanese national identity, not its weakness.--Provided by publisher.